Revision of some ophiuroid records (Echinodermata: Ophiuroidea) from Argentina - Brogger, Martin Ignacio (2015)
The taxonomy of some ophiuroids reported from off Argentina, western Antarctica and the SW Atlantic Ocean is reviewed. The species Amphilepis sanmatiensis, known only from the small holotype, is a synonym of Amphioplus lucyae. This synonymy removes the only reported endemic ophiuroid from Argentina. The species name ?Ophiacantha ingrata Koehler, 1923? used for specimens from South Georgia is invalid; the specimens are likely to belong to one of two cryptic species within the O. vivipara complex. Specimens of Amphiura joubini reported from Argentina are re-identified as Amphiura princeps, and specimens of Ophiactis amator from the Antarctic Peninsula are re-identified as Ophiactis asperula.